Sastra sebagai materi pembelajaran BIPA berwawasan interkultural - Dwi Budiyanto (Jurnal Bahasa Indonesia bagi Penutur Asing, 2022)
Literary works are authentic representations of society's socio-cultural reality. On this basic principle, literary works are particularly appropriate for use as teaching materials in international language learning.  This qualitative descriptive study aimed to identify Indonesian literary works that can be used as teaching materials for BIPA learning, as well as to construct BIPA learning designs using literature as teaching materials from an intercultural perspective. The research data originated from the works of Indonesian authors, including Clara Ng's Dongeng Tujuh Menit --which contains seven stories, Umar Kayam's Lebaran di Karet, di Karet..., and Kuntowijoyo's Impian Amerika --which contains 30 stories. Data in the form of discourse units, phrases, clauses, sentences, and words relevant to the study's focus were analyzed using Lazar, Bibby & McIllroy, and the CEFR category in grading the ability of foreign language learners to determine its relevance as teaching material from a linguistic standpoint. Repeated readings (semantic validity), referral to relevant reference materials (referential validity), and discussions with peers (interater reliability) were all used to establish the data's validity. The study's findings were as follows. First, literary works relevant to BIPA learning from an intercultural perspective were identified, with the “Cerita Wayang Sebelum Tidur” and “Padi Merah Jambu” by Clara Ng being appropriate for intermediate (B2) students, while the short stories “Lebaran di Karet, di Karet...” by Umar Kayam and “Aku Cinta Indonesia” by Kuntowijoyo being appropriate for advanced BIPA students (A2). Second, based on Liddicoat's (2011) intercultural learning model (interacting), BIPA learning with intercultural insight by using literary works as teaching materials is designed with four cyclical steps, namely (1) paying attention (noticing), (2) comparing (comparing), (3) reflecting (reflecting), and (4) interacting